Empowering Muslim Women In Nigeria: An Analysis Based On Nigerian Muslim Scholars - Abdullahi, Mohammed (2021)
Historically, women have been regarded as constituting a weaker section in the society. However, they are historically responsible for developing future generations. While women empowerment serves in granting economic independence to women, it also serves in contributing to the economic benefits of the household and the society. Muslim women in Nigeria often face many challenges and discriminatory practices due to the influence of the various customs in many parts of Nigeria. There is paucity of research about contexts underlying empowering Muslim women in Nigeria based on Nigerian Muslim scholars. Thus, understanding factors that underpin empowering Muslim women in Nigeria based on Nigerian Muslim scholars is vital in designing interventions. The study adopted library research methodology which was supplemented by qualitative primary research. The objectives of the study were to understand Nigerian Muslim Scholars perspectives on the empowerment of muslim women; to examine the position of Muslim women regarding women empowerment in Nigeria; identify the position of Islam regarding empowerment activities of Muslim women in Nigeria; and to examine the ways through which Muslim women empowerment be improved to attract more women into empowerment activities in Nigeria. Primary data was collected through 10 (ten) e-mail interviews (5 Islamic study lecturer from universities and other higher educational Institutions in Nigeria, as well as 5 officials of Government and Non-Governmental Organizations in Nigeria).